2020
DOI: 10.3390/microorganisms8020207
|View full text |Cite
|
Sign up to set email alerts
|

The Root Nodule Microbiome of Cultivated and Wild Halophytic Legumes Showed Similar Diversity but Distinct Community Structure in Yellow River Delta Saline Soils

Abstract: Symbiotic associations between leguminous plants and their nodule microbiome play a key role in sustainable agriculture by facilitating the fixation of atmospheric nitrogen and enhancing plant stress resistance. This study aimed to decipher the root nodule microbiome of two halophytic legumes, Sesbania cannabina and Glycine soja, which grow in saline soils of the Yellow River Delta, China, using PacBio’s circular consensus sequencing for full-length bacterial 16S rRNA gene to obtain finer taxonomic information… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 28 publications
(41 reference statements)
3
18
0
Order By: Relevance
“…A total of 1,528 ± 39 and 1,797 ± 246 OTUs were obtained from the clean sequences from the SDY and Ss root zones, respectively ( Supplementary Table S1), whereas only 358 ± 209 and 164 ± 10 OTUs were obtained from the nodules of wild soybean grown in these regions, respectively. We found that the barren sand root zone carried more OTUs than the fertile soil; however, our previous study identified 191 ± 13 OTUs in nodules using PacBio's circular consensus sequencing for full-length bacterial 16S rRNA (Zheng et al, 2020), similar to the 164 ± 10 OTUs obtained here. The dataset was rarefied to an even sequencing depth of 20,000 sequences and 2,423 bacterial OTUs were identified.…”
Section: Bacterial Community Composition In the Root Zone Of Saline-asupporting
confidence: 84%
See 2 more Smart Citations
“…A total of 1,528 ± 39 and 1,797 ± 246 OTUs were obtained from the clean sequences from the SDY and Ss root zones, respectively ( Supplementary Table S1), whereas only 358 ± 209 and 164 ± 10 OTUs were obtained from the nodules of wild soybean grown in these regions, respectively. We found that the barren sand root zone carried more OTUs than the fertile soil; however, our previous study identified 191 ± 13 OTUs in nodules using PacBio's circular consensus sequencing for full-length bacterial 16S rRNA (Zheng et al, 2020), similar to the 164 ± 10 OTUs obtained here. The dataset was rarefied to an even sequencing depth of 20,000 sequences and 2,423 bacterial OTUs were identified.…”
Section: Bacterial Community Composition In the Root Zone Of Saline-asupporting
confidence: 84%
“…Based on relative abundance, the most common phyla (>0.1%) in the coastal nodule samples (nS) and Yellow River Delta nodule samples (nD), respectively, were Proteobacteria (98.458 ± 0.045 and 99.703 ± 0.002%), Actinobacteria (0.533 ± 0.340 and 0.167 ± 0.047%), Bacteroidetes (0.177 ± 0.158 and 0.037 ± 0.017%), Chloroflexi (0.123 ± 0.122 and 0.047 ± 0.009%), Acidobacteria (0.113 ± 0.092 and 0.043 ± 0.012%), and Gemmatimonadetes (0.117 ± 0.095 and 0.043 ± 0.009%), indicating that nS samples displayed a higher diversity and proportion than nD samples. As predicted, the most prominent Proteobacteria were Sinorhizobium/Ensifer (97.330 ± 1.701 and 98.661 ± 0.471%); however, the proportion differed (85.67 ± 6.29%) from PacBio's circular consensus sequencing for full-length bacterial 16S rRNA gene in nD samples (Zheng et al, 2020).…”
Section: Identification Of Nodule Bacterial Community Compositionsupporting
confidence: 61%
See 1 more Smart Citation
“…Nodule microbiome analysis of rhizobial populations shows the Bradyrhizobium genus as the predominant mung bean micro-symbiont in Brazilian tropical soils independent from both plant genotypes and whether soil samples present (or do not) a history of mung bean cultivation. A predominance of a rhizobial genus in legume nodules is commonly reported ( Sharaf et al, 2019 ; Hakim et al, 2020 ; Rocha et al, 2020 ; Zheng et al, 2020 ). Isolation of diazotrophic strains from mung bean nodules cultivated in different soils worldwide have shown a predominance of Bradyrhizobium strains ( Yang et al, 2008 ; Zhang et al, 2008 ; Appunu et al, 2009 ; Risal et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…A NanoDrop 2000 spectrophotometer (Thermo Scientific, Waltham, Massachusetts, USA) was used to assess the quality and concentration of soil DNA. A sequencing library was prepared using primers sets 27F/1492R [ 22 , 23 ] and ITS9munngs/ITS4ngsUni [ 24 ] to amplify the 16S rRNA gene and ITS. PCR conditions were 95°C for 5 min, followed by 30 cycles of 95°C for 30 s, 55°C for 30 s, and 72°C for 1min 30 s, with a final extension at 72°C for 7 min (GeneAmp 9700, ABI, California CA, USA).…”
Section: Methodsmentioning
confidence: 99%